(untitled) (Acta Scientiarum. Biological Sciences, 2021)
We investigated changes in the species richness, abundance, and composition of the zooplankton community in response to the formation of a small reservoir in the Caveiras River, southern Brazil. Zooplankton were collected using a motor-pump and a plankton net (68 Î¼m mesh), with 600 L of water filtered per sample. Sampling occurred during the pre- (April, August, and December 2011) and post-impoundment (July and October 2013, and January 2014) phases of the Caveiras River. We identified 86 taxa in this study, and rotifers were the predominant group. The species richness and abundance of the zooplankton increased after the filling of the reservoir. Furthermore, the zooplankton community showed a clear change in the species composition between the phases before and after the formation of the reservoir, with the emergence of typical planktonic species. Changes in the structure of the zooplankton community were related to changes in limnological characteristics due to the impoundment of the river, mainly in the availability of food and in the concentration of nutrients.